Reorganization of Islamic Banking: A New Proposal (American Journal of Islam and Society, 1987)
IntroductionTraditional banking is rejected by Islamic scholars mainly because of interest.Interest-bearing banking is supposedly being replaced by profit-sharingbanking organized on the basis of two-tier mudambu. Seigniorage (differencebetween face value and intrinsic value of money) resulting from expansionin demand deposits will continue accruing to the interest-free banking system.Islamic economists consider it unjust to leave the seigniorage in the handsof private banks.Money experts feel strongly that the seigniorage should be transfered tosociety by financing welfare projects. A dual banking scheme is proposedhere that will accomplish this task and contribute towards achievement of someother socio-economic goals of an Islamic society.The major role of banlung for an economy is presented in section I. Interestfreebanlung is outlined in section II. Dual banlung scheme, with its justificationand socio-economic implications, is proposed in the final section.I. General Role of BankingEconomists classify all economic agents into households, business firms,and government. An economic dgent must operate within its budget constraint.The budget of an economic unit could be balanced, in deficit, or insurplus for a given period depending on, respectively, whether its incomematches its expenditures, income exceeds its expenditures, or expendituresexceed its income. Savings from the surplus economic units (SEU) are transferredto the deficit economic units (DEU)in order to satisfy current investmentand consumption needs of DEUs and increase incomes of SEUs for the ensuing ...